Consumers Responses to Traditional and Non Traditional Advertisements - Sarwar, Huma (Advances in Social Sciences Research Journal, 2017)
This study addresses these challenges posed by new emerging marketing landscape shaped by technological advancement where consumers use a firm’s multiple channels to purchase multiple categories and firm employs both traditional and new media to reach their consumers. The digital world not only allows consumers to embrace new channels in much more active ways facilitated by various communication media but also is transforming how consumers shop, live, develop and interact. Therefore, it is very important for retailers to understand not only the shopping behavior across multiple channels in multiple categories but also the effectiveness of various communication media across categories. Understanding such behavior across multiple channels influenced by multiple touch-points or multiple communication media adopted by firms will facilitate better allocation of resources to attract multichannel consumers.